Tingkat Erodibilitas Tanah Di Daerah Aliran Sungai Bayang Sani - Siswandana Siswandana; M. Iqbal Liayong Pratama; Hary Febrianto; Maijem Simponi (Universitas Negeri Gorontalo, 2020)
The Bayang Sani Watershed has an area of 1267.97 hectares with an average rainfall of 3117 mm/ year. The topography of this watershed have varies slopes. In the rainy season, the river water is a muddy color and both soil and rocks are contained in the river’s water that causes channel damage and reduced river capacity. It is caused by the wider distribution of land erosion in the Bayang Sani Watershed. The purpose of this study was to analyze the soil erodibility. The method of this study is a quantitative study and field survey method. The data was collected by field survey and sample points were determined using purposive random sampling techniques. The sample was analyzed in the BPTP laboratory to determine the types and colors of the soil sample, depending on the quality of the soil's erosive value. The results show that soil erodibility in the Bayang Sani Watershed range 0.15-0.28. The low soil erodibility level found in land units F3.II.Kc.Qal.Lat (0.16), V2.II.Kc.Tomp.Lat (0.15) and V2.II.Sm.Tomp.Lat. (0.16) the moderate of soil erodibility was found in the land unit V3.III.Ht.Tomp.Lat (0.28).